1994
DOI: 10.1007/bf01401464
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cerebral ischaemia: The pathological substrate

Abstract: Ischaemic complications both at the level of the cortex and the hypothalamus are well recognised after an aneurysmal subarachnoid haemorrhage. We have studied histological changes in the cortex (53 patients) and hypothalamus (48 patients) in patients who died after an aneurysmal subarachnoid haemorrhage. Cortical ischaemic lesions were demonstrated in 41 of the 53 patients studied. These changes were more common in patients who had impaired control of systemic blood pressure (p = 0.0004) and in patients who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 31 publications
7
74
0
Order By: Relevance
“…Although pathologic changes are found in all layers of vasospastic vessels, ranging from concentric intimal thickening by subendothelial fibrosis to necrosis in the tunica media, pathologic findings are not restricted to the vessel wall alone (Hughes and Schianchi, 1978). Microthrombi were detected for the first time in 1983 upon autopsy in a patient with cerebral infarction after SAH, and later confirmed in other studies (Suzuki et al, 1983(Suzuki et al, , 1990Neil-Dwyer et al, 1994;Stein et al, 2006). In an autopsy study investigating six SAH patients, including four patients who supposedly died from DCI, it was observed that patients who die from delayed ischemia have significantly more microthrombi in clinically ischemic regions and in areas showing cerebral infarction on computed tomographic scan, when compared with patients who die from rebleeding or acute hydrocephalus (Suzuki et al, 1990).…”
Section: Evidence From Autopsy Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…Although pathologic changes are found in all layers of vasospastic vessels, ranging from concentric intimal thickening by subendothelial fibrosis to necrosis in the tunica media, pathologic findings are not restricted to the vessel wall alone (Hughes and Schianchi, 1978). Microthrombi were detected for the first time in 1983 upon autopsy in a patient with cerebral infarction after SAH, and later confirmed in other studies (Suzuki et al, 1983(Suzuki et al, , 1990Neil-Dwyer et al, 1994;Stein et al, 2006). In an autopsy study investigating six SAH patients, including four patients who supposedly died from DCI, it was observed that patients who die from delayed ischemia have significantly more microthrombi in clinically ischemic regions and in areas showing cerebral infarction on computed tomographic scan, when compared with patients who die from rebleeding or acute hydrocephalus (Suzuki et al, 1990).…”
Section: Evidence From Autopsy Studiessupporting
confidence: 65%
“…No distinction was made between the presence of microthrombi in symptomatic and asymptomatic vasospastic vessels. However, because microclots are not only present in regions with clinical signs of delayed ischemia or infarction but are widespread in the brain, an additional factor is apparently necessary for the development of clinical signs of focal cerebral ischemia (Suzuki et al, 1990;Neil-Dwyer et al, 1994;Stein et al, 2006). This is supported by a recent autopsy study that investigated 29 SAH patients and showed pathologic evidence of ischemia in 93% patients, but clinical signs of DCI were present in only 48% of the studied patients (Stein et al, 2006).…”
Section: Evidence From Autopsy Studiesmentioning
confidence: 85%
“…This assumption is in accordance with the anterior location of 85% of all saccular aneurysms and has been supported by pathological studies. 22,23 In the present study, a phantom model was designed to simulate the anatomy of the perforating arteries characterized both by a right-angle bifurcation with the parent artery as well as an abrupt decrease in lumen diameter. Although the diameter of the tubes used in the model was significantly larger than that of cerebral arteries, the relative proportions between main cerebral and perforating arteries was respected.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is further supported by postmortem studies after SAH showing small brain infarction in cerebral territories supplied by perforating arteries. 22,23,26 This clinical situation, however, is more likely to be relevant to the vertebrobasilar system, where vasospasm is most commonly focal and therefore exposes those perforators that branch out of the postvasospastic portion of the parent vessel. 27 These results may also explain the occurrence of severe and prolonged consciousness impairment due to local cerebral vasospasm even in those patients who do not present with motor deficit or crude brain infarction on CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, it is implicitly suggested that DCI is always caused by arterial narrowing of the cerebral arteries, which often is not the case. [32][33][34][35] Therefore, as long as the pathogenesis of DCI is incompletely known, it is preferable to use a term that describes the clinical picture and in which no assumption is made about its pathogenesis. Delayed neurological deficit is a general term, without any assumption about pathogenesis and cause.…”
Section: Considerations For Uniform Terms and Definitionsmentioning
confidence: 99%